2018
DOI: 10.1080/01480545.2018.1481085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levothyroxine on learning and memory deficits in a rat model of Alzheimer’s disease: the role of BDNF and oxidative stress

Abstract: The effect of levothyroxine (L-T4) on the learning and memory impairment induced by streptozotocin (STZ) and brain tissue oxidative damage in rats was evaluated. An animal model of the Alzheimer's disease (AD) was established by intracerebroventricular injection of STZ (3 mg/kg) in male Wistar rats (250 ± 50 g). After that, the rats were treated for 3 weeks with L-T4 (10, 100 μg/kg) or normal saline. Passive avoidance (PA) learning and spatial memory were evaluated using shuttle box and Morris water maze (MWM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Whereas in intact mature neurons, BDNF downregulated KCC2 (39, 62, 63), in injured neurons BDNF upregulated KCC2 (8, 61, 62). Interestingly, TH have been shown to increase the expression of BDNF in lesioned slices of the hippocampus (18, 64) and other pathological models (1517). We can then assume that an acute L-T4 treatment after UVN induces a local increase of BDNF in the deafferented VN, thus promoting cell proliferation as demonstrated in our previous study (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in intact mature neurons, BDNF downregulated KCC2 (39, 62, 63), in injured neurons BDNF upregulated KCC2 (8, 61, 62). Interestingly, TH have been shown to increase the expression of BDNF in lesioned slices of the hippocampus (18, 64) and other pathological models (1517). We can then assume that an acute L-T4 treatment after UVN induces a local increase of BDNF in the deafferented VN, thus promoting cell proliferation as demonstrated in our previous study (8).…”
Section: Discussionmentioning
confidence: 99%
“…TH signalling governs many aspects of neurogenesis, including proliferation, survival, migration, differentiation and maturation of neuronal and glial cells (11)(12)(13)(14). Thyroxine (T4) or triiodothyronine (T3) injections have been shown to increase the expression of BDNF in different pathological models (stroke : (15,16), Alzheimer disease: (17), and axotomy (18)). In addition, several studies have demonstrated the protective role of TH and their ability to promote functional recovery through genomic and non-genomic actions (for review see (19,20)).…”
mentioning
confidence: 99%
“…In these trails, the rats were placed in the light chamber and an entering delay of the rat to the dark chamber was then measured as the latency time. Additionally, the time spent by the animal in the dark and light compartments was recorded (Bavarsad et al 2020). Notably, in retention trails, the shock punishment was not applied.…”
Section: Behavioral Assessments Morris Water Maze (Mwm) Testmentioning
confidence: 99%
“…Subsequently, the obtained mixture was heated in boiling water and after 40 min, the samples were cooled and the absorbance was spectrophotometrically measured at 412 nm. The following equation was used to calculate the concentration of MDA (Bavarsad et al 2020). Concentration (M) = Absorbance / 1.56 × 10 5 .…”
Section: Assay Of Lipid Peroxidationmentioning
confidence: 99%
“…The testing session was performed on 2, 24, and 48 hr after delivering the foot shock. In this session, the animals were placed back into the illuminated compartment and the time taken by the animals to enter the dark part, the entries made by the animals and the time spent in there during the 5 min of the test was recorded (Bavarsad et al, 2020).…”
Section: Passive Avoidancementioning
confidence: 99%